Change to the Retirement Age Limit as an Element of Rationalisation of Pension Expenses - Klimkiewicz, Aldona (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
It is part of the social and economic policy to gradually raise the retirement age up to 67 years for both genders, aimed at reduction of effects of unfavourable changes in the age structure of the society, and staving off the crisis of public finances. The raised retirement age should imply gradual increase of social insurance funds based on pension contributions, and rein in expenses on benefits paid. Because of quite a long time frame, it is difficult to say whether or not the raised retirement age will be a success. Therefore, in order to make the reform successful it is necessary to carry out concurrent actions concerning education, health protection, labour market, etc. It is vital to take effective measures in the social and economic sphere aimed at providing older employees with workplaces that would motivate them to remain professionally active for longer. If such circumstances in the country's social and economic policy were overlooked, the success of the age raising itself would be at risk, and it might produce some adverse effects like increased unemployment rates, especially among employees at the pre-retirement age.